2018
DOI: 10.3389/fncel.2018.00193
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Astrocytes in Neuro-Vascular Unit and the Tripartite Synapse With Emphasis on Reactive Gliosis in the Context of Alzheimer’s Disease

Abstract: Astrocytes, which are five-fold more numerous than neurons in the central nervous system (CNS), are traditionally viewed to provide simple structural and nutritional supports for neurons and to participate in the composition of the blood brain barrier (BBB). In recent years, the active roles of astrocytes in regulating cerebral blood flow (CBF) and in maintaining the homeostasis of the tripartite synapse have attracted increasing attention. More importantly, astrocytes have been associated with the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 163 publications
2
89
0
Order By: Relevance
“…In later stages of the inflammatory process astrocytes become a prominent source of anti‐inflammatory or immune regulatory molecules, such as interleukin 10 or TGF‐ß, as even shown in the human brain (Machado‐Santos et al, ). In line with these observations, polarization into proinflammatory A1 and anti‐inflammatory A2 astrocytes, which is similar to M1 and M2 polarization of microglia, has been described in vitro and in vivo (Liu, Yang, Ju, Wang, & Thang, ), although with different profiles between mouse and human astrocytes (Tarassishin, Suh, & Lee, ).…”
Section: Astrocytes In Experimental and Human Inflammatory Brain Diseasesupporting
confidence: 62%
“…In later stages of the inflammatory process astrocytes become a prominent source of anti‐inflammatory or immune regulatory molecules, such as interleukin 10 or TGF‐ß, as even shown in the human brain (Machado‐Santos et al, ). In line with these observations, polarization into proinflammatory A1 and anti‐inflammatory A2 astrocytes, which is similar to M1 and M2 polarization of microglia, has been described in vitro and in vivo (Liu, Yang, Ju, Wang, & Thang, ), although with different profiles between mouse and human astrocytes (Tarassishin, Suh, & Lee, ).…”
Section: Astrocytes In Experimental and Human Inflammatory Brain Diseasesupporting
confidence: 62%
“…4,8 In more recent years, the crucial role of astrocytes in neuronal synaptic transmission has been elucidated, giving rise to the concept of the “tripartite synapse”. 1,2,9…”
Section: Mainmentioning
confidence: 99%
“… The tripartite synapse, consisting of the presynaptic neuron, post-synaptic neuron, and an astrocyte, is considered to be the main locus of signaling between neurons in the brain. 1,2 Neurotransmission is energetically very expensive 3,4 , and the primary neurotransmitter utilized for signaling is glutamate. It has been found that glutamate is also used as a substrate for energy generation.…”
mentioning
confidence: 99%
“…It has been shown that human astrocytes can secrete molecules associated with inflammation such as interleukins, as well as chemotactic factors such as MCP‐1, macrophage inflammatory protein‐1α and interferon‐γ‐inducible protein 10 . It was reported that astrocytes are actively involved in the secretion of pro‐inflammatory molecules IL‐6 and interferon (INF)γ . Additionally, oestradiol has the ability to decrease the secretion of these inflammatory molecules in an oxidative model mediated by H 2 O 2 following stimulation with lipopolysaccharide (LPS), for which the response is associated with the NF‐κB pathway .…”
Section: Oestrogens and The Brainmentioning
confidence: 99%